Pemanfaatan Tanaman Refugia sebagai Pestisida Nabati untuk Mengurangi Serangan Hama pada Sistem Budidaya Hidroponik: Utilization of Refugia Plant as a Biopesticide to Reduce Pest Attack on Hydroponic Cultivation Systems - Tri Candra Setiawati; Sigit Prastowo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Cultivation of plants by utilizing a small area can be developed, especially during a pandemic, among others, by using a hydroponic system. Vegetable yields (pakcoy, lettuce) do not always have good quality due to pest attacks, including in the hydroponic system, resulting in a decrease in both quantity and quality, which affects the income and turnover of this micro-enterprise (UMKM). The objectives of this service are 1) provide knowledge and skills in making biopesticides based on refugia plants or organic pesticides (“pestisida nabati”) in order to improve the quality and quantity of production, and 2) The practice of “pestisida nabati” application for hydroponic cultivation. Service activities are carried out with the following methods: providing material and discussion, making vegetable pesticides/biopesticides, and applying “pestisida nabati”  in hydroponic cultivation in Micro Business Groups (UMKM "Ini Hydroponics." Accordingly, 12 participants in the training for making biopesticides and their application were practitioners, partners, and students interested in developing hydroponics. The training on making biopesticides with the essential ingredients of mischievous (Cosmos caudatus) and neem leaves (Azadirachta indica) has resulted in a solution of vegetable pesticides ready to be applied in hydroponic cultivation. The spraying application is carried out on the first day after the biopesticide is made and a week later. Based on observations of the quality of lettuce harvested a week after spraying, the product obtained showed a lower pest attack than before.